Migration of an AXIOS stent complex into the colon – A case report. (January 2021) - Tran, Steven; Neo, Eu Nice
Highlights: There is increasing use of endoscopic ultrasound-guided drainage stents. Stent migration is a rare complication of lumen-apposing metallic stents. Conservative management of migration is feasible if there are no complications. Abstract: Introduction: Pancreatic fluid collections are a common complication of acute pancreatitis. They are classified as acute peripancreatic fluid collections and pancreatic pseudocysts. There has been an increase in the use of endoscopic ultrasound-guided drainage stents for management of these collections. As a result, complications such as stent migration are becoming more prevalent. Presentation of case: A 47-year-old male presented to the emergency department with upper abdominal pain, nausea and vomiting, and intermittent fevers. The patient had a known history of a pancreatic pseudocyst. He had undergone an endoscopic cyst-gastrostomy and placement of an AXIOS and Compass stents for drainage prior to the current presentation. The patient was investigated with a computed tomography (CT) scan that demonstrated acute pancreatitis, and migration of his AXIOS/Compass stent complex into the transverse colon. The patient was managed conservatively, and ultimately passed the stent through his bowel motions without issue. Follow up abdominal x-ray confirmed the passage of the stent. Discussion: Stent migration is a recognised complication of stent placement but is infrequently described for lumen-apposing metal stents like the AXIOS stent. The AXIOS stent has a dumbbell configuration designed to reduce the rate of migration compared to the original double-pigtail plastic stents. Despite this, stent migration still occurs, as in this case. Conclusion: Complications of AXIOS stents can also include migration of the stent despite their specific design to prevent this. Conservative management is feasible rather than endoscopic retrieval and can be considered if there are no complicating features.